DEVELOPING ABILITY IN ANSWERING READING QUESTION BY USING QUESTION-ANSWER RELATIONSHIPS TECHNIQUE - Marliasari Sherly (JAMBI-ENGLISH LANGUAGE TEACHING, 2016)
The ability to comprehend the reading text is very crucial to assess the students’ understanding towards what they have read. The main goal is to derive some understanding of what the writer is trying to convey and make use of that. Unless the reader cannot gather any information and use it to efficiently function. A technique called Question-Answer Relationship (QARs) was used to assist students to gain the ability to comprehend the text. This technique was technically used to identify the type of response necessary to answer question. This technique requires the students to distinguish when it is appropriate to use background knowledge or textual information to answer the question. The objectives of this study were to find out the significant differences between students’ ability in answering questions of reading text, and to figure out whether the QARs technique were able to develop students ability in answering questions of reading text. The population of the study was all of the eighth graders of SMP Negeri 1 Lembak consisting of 139 students from 5 classes. 60 students were selected by using cluster random sampling method and the samples were divided into two groups, experimental and control group. The test consisted of 40 multiple choice questions. The result of data analysis showed that t-obtained 2.006, where the critical 1.67, at the significance level of 5% and df 52. This showed that there were any significant differences in students’ ability in answering the question between the students who were taught by QARs and those who were not. And through this study, teaching reading by using question-answer relationships technique can significantly develop the students’ ability especially to the eighth graders at SMP Negeri 1 Lembak. Keywords: comprehension, question-answer, reading text